RSIS Series on Malaysia's 14th General Election - Black Swan, Dark Horse, and Elephant in the Room - Liow, Joseph Chin Yong (2018)
As Malaysians prepare to vote in the 14th general election on 9 May 2018, three key features mark the country’s most crucial political struggle in years.